LAND OF OBLIVION (LA TERRE OUTRAGÉE, 2012) BY MICHALE BOGANIM AS A POSTTRAUMATIC FILM - Waligórska-Olejniczak, Beata (Porównania, 2019)
LAND OF OBLIVION (LA TERRE OUTRAGÉE, 2012) BY MICHALE BOGANIM AS A POSTTRAUMATIC FILM. “PORÓWNANIA” 1 (24), 2019. Vol. XXIV, P. 85-94. ISSN 1733-165X. The aim of the article is the analysis of Michale Boganim’s film Land of Oblivion from the point of view of contemporary trauma and memory studies. Taking advantage of the scientific notions worked out in the field of those studies, it is stated that the work can be regarded as a posttraumatic film first of all on account of its core problem, which is the Chernobyl disaster and its consequences shown through the prism of the milieu. Boganim encodes the trauma of the witness in the body and mind of the human being who is not able to work through it. Badly located nostalgia, melancholy and kinetic hyperactivity function in the film as signs which allow the audience to take part in the tragedy of the characters, a kind of repetitive code motivating the reflection on the mechanisms of remembering and forgetting.